2020
DOI: 10.1002/cpdd.860
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Bioequivalence Estimation of Two Formulations of Alfuzosin Extended‐Release Tablets

Abstract: Alfuzosin is a medication approved by the US Food and Drug Administration to treat benign prostatic hyperplasia symptoms. Bioequivalence studies are demanded by regulatory authorities to evaluate the expected in vivo biological similarity of 2 formulations of a medication. The aim of this study is to assess the bioavailability of the generic (test) and branded (reference) formulations of 10-mg alfuzosin extended-release tablets after oral administration to healthy adults under fed conditions. The study used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The investigated method showed a satisfying sensitivity for detection of TDF and AFH in human plasma samples spiked with them. It was reported by pharmacokinetic studies that AFH showed concentrations of 2–12 ng ml −1 in plasma and 1–5 ng ml −1 in urine [57], while TDF showed plasma concentrations of 50–320 ng ml −1 and urine concentration of 25 ng ml −1 [58].…”
Section: Resultsmentioning
confidence: 99%
“…The investigated method showed a satisfying sensitivity for detection of TDF and AFH in human plasma samples spiked with them. It was reported by pharmacokinetic studies that AFH showed concentrations of 2–12 ng ml −1 in plasma and 1–5 ng ml −1 in urine [57], while TDF showed plasma concentrations of 50–320 ng ml −1 and urine concentration of 25 ng ml −1 [58].…”
Section: Resultsmentioning
confidence: 99%
“…The lack of analysis leaves opens the possibility that the dykes are from Tertiary basalt volcanism. In the Al Hara region, Abo Saada. (1982);reported in Al Saifi et al, (1983) assessed 2400 Joints and found that they were ENE/dip SE; NW/SW and NE; EW/gentle to subhorizontal; and NS/vertical.…”
Section: Geological Setting Of Al Taif Areamentioning
confidence: 99%
“…LC with fluorescence detection has also been applied for the same purpose (Cui et al, 2017; Guo et al, 2021; M. He, Wang, & Wei, 2016; Huang et al, 2018; Huo et al, 2014). However, LC tandem mass spectrometry (HPLC–MS/MS) provides higher sensitivity and selectivity (Al Bawab et al, 2020; Alhusban et al, 2021) and has been employed successfully for the determination of various neurotransmitters in brain tissues (Forgacsova et al, 2018; B. He et al, 2013; He, Zhao, et al, 2016; Helmschrodt et al, 2020; Kim et al, 2014; Kuang et al, 2019; Lin et al, 2019; Liu et al, 2018; Nirogi et al, 2010; Olesti et al, 2019; Sørensen & Johannsen, 2019; H. Wang et al, 2012; Wojnicz et al, 2016; Zheng et al, 2017; Zhou et al, 2015).…”
Section: Introductionmentioning
confidence: 99%